Genotypic characterization of Phytophthora infestans populations in Bangladesh - Wharton, P.; Dangi, S.; Begum, M. M.; Douches, D.; Hokanson, K. E.
Late blight, caused by Phytophthora infestans, is an economically important disease of potato that causes significant yield losses, with severe outbreaks regularly occurring in Bangladesh. The objective of this study was to do a large-scale survey of potato fields in the main potato-growing divisions of Bangladesh examining genotypic diversity of P. infestans populations. A total of 160 samples were collected in 2018 from both potato (n?=?140)and tomato (n?=?20). Isolates were mainly collected on FTA cards (n?=?143), but 17 were also collected and isolated into pure culture. Microsatellite analysis revealed high levels of subclonal diversity in P. infestans populations with 116 multilocus genotypes recorded from 160 samples. Comparisons with standards of European and US isolates showed that 74 percent of samples could be categorized as genotype EU_13_A2, 7 percent clustered near EU_6_A1 and EU_1_A1, and 19 percent were unique. Discriminant analysis of principal components showed that the P. infestans population clustered into four distinct groups: a main group that contained most of the samples from potato, two distinct tomato groups and one group of samples originating from the division of Mymensingh. Of 17 isolates from cultures, 16 were EU_13_A2 and one was EU_6_A1; 15 were insensitive to metalaxyl-M. Out of 160 samples, 158 were categorized as mating type A2 and two as mating type A1. These results indicate that Bangladesh populations of P. infestans from potato, like those from neighbouring countries, are dominated by genotype EU_13_A2. However, populations from tomato were distinct and appear to be specific to tomato.
Keywords: FTA CARDS; GENETIC STRUCTURE; LATE BLIGHT; MICROSATELLITE ANALYSIS; PHYTOPHTHORA INFESTANS; POTATO